DUMMY BOOK IoT: PANDUAN VISUAL KONSEP DAN IMPLEMENTASI IoT - Maisura, Mira; Yuliana, Cut Putroe; Ridwan, Ridwan; Alifa, Fatin; Maulidza, Chairunnisa (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The Industrial Revolution 4.0 demands the integration of technological literacy such as the Internet of Things (IoT) into the educational curriculum. However, the main obstacles at the high school/Islamic high school level are the lack of affordable, practical, and context-appropriate IoT training media, limited school infrastructure, and competent resources. This study aims to develop an IoT dummy boom that can be used as a suitable IoT training media for use in learning. The development method applied is a 4D model with stages of define, design, develop, and dissemination. The use of the 4D model ensures quality control of the media. The results of the media feasibility test obtained an average value of 4.414 (on a Likert scale), which indicates that 92.45% of the total respondents agreed that the media is very suitable and feasible to use.